Limits to Right of Information of the Shareholder in the Social Responsibility Pretension - Kossuth Wieland, Alfred (2015)
Considering the importance of social responsibility claim for the company, shareholders and creditors, it is necessary to analyze whether the right of member information is appropriately protected when an action of this nature is promoted.